Green and blue areas as predictors of overweight and obesity in an 8‐year follow‐up study. (28th April 2014) - Halonen, Jaana I.; Kivimäki, Mika; Pentti, Jaana; Stenholm, Sari; Kawachi, Ichiro; Subramanian, S.V.; Vahtera, Jussi
<x xml:space="preserve">Abstract</x> Objective To longitudinally examine associations between proximity of urban green or blue areas and BMI. Methods The study population consisted of the Finnish Public Sector study participants who responded to surveys in 2000 and 2008 and lived in an urban area; 15, 621 of them did not move residence (nonmovers) during the follow‐up, and 9696 did (movers). The associations for objectively measured distance and change in distance to blue area and usable green area with self‐reported BMI were assessed (normal weight/overweight/obese). Results Among the nonmovers, living >750 versus <250 m from usable green area increased the odds of overweight (odds ratio [OR] 1.50; 95% confidence interval [CI] 1.07‐2.11), and living 500‐750 versus <250 m from the nearest blue area increased the odds of overweight (OR 1.24; 95% CI 1.01‐1.52). No significant associations were observed for obesity. Moving away from the proximity of green, but not blue, area (from <250 to >250m) increased the odds of obesity (OR 1.49; 95% CI 1.08‐2.06). Conclusions These longitudinal population level findings suggest that living far from usable green areas or waterfront in urban areas increases the risk of overweight.